Disposable electrochemical sensors for healthcare monitoring : material properties and design - Pandikumar, A.; Devi, K. S. Shalini (Royal Society of Chemistry, 2021)
The book focusses on the emerging disposable electrochemical sensors in the health sector and advancement of analytical devices to monitor diabetic, cancer and cardiovascular patients using different nanomaterials.
Keywords: Electrochemical sensors.; elektronické knihy; electronic books